Seigneurial Hermeneutics - Queiroz, Marcos (2024)
The text develops the concept of seigneurial hermeneutics based on the dialogue between Ronald Dworkin and Machado de Assis. First, the main elements of what Dworkin calls the “chain novel” are exposed. Subsequently, the text develops criticism of the modern novel present in the work of Machado de Assis. This criticism is a stylization of the domination patterns of the seigneurial class in Imperial Brazil. Finally, Machado's literature reveals long-lasting characteristics of the interpretation of law in Brazil, which we call seigneurial hermeneutics: the fickle, incongruous and arbitrary manipulation of the legal system; the principle of illegality; the legal ritualization of sacrificial violence; and the absolute conception of property.